Quantifying the Pulmonary Risks of Volcanic Gas Inhalation: A Meta-Analysis - Putri, Septriana; Yessy Susanty Sabri (HM Publisher, 2025)
Background: Volcanic eruptions release a complex mixture of gases and particulate matter, posing significant respiratory health risks. This meta-analysis aims to quantify the association between volcanic gas inhalation and adverse pulmonary effects. Methods: A systematic search of PubMed, Scopus, and Web of Science was conducted for studies published between 2013 and 2024 investigating the respiratory effects of volcanic gas exposure. Studies reporting quantitative data on lung function, respiratory symptoms, or disease prevalence were included. Random-effect models were used to pool effect estimates, and heterogeneity was assessed using the I² statistic. Results: Six studies (n = 2,215 participants) met the inclusion criteria. Volcanic gas exposure was associated with a significant decrease in FEV1 (forced expiratory volume in 1 second) (standardized mean difference [SMD] = -0.55, 95% CI: -0.67 to -0.42, I² = 51%), increased prevalence of asthma (odds ratio [OR] = 3.31, 95% CI: 1.84 to 5.96, I² = 76%), and chronic bronchitis (OR = 2.86, 95% CI: 1.97 to 4.15, I² =0%). Subgroup analysis revealed a stronger association between gas exposure and respiratory effects in children and individuals with pre-existing lung conditions. Conclusion: This meta-analysis provides compelling evidence that volcanic gas inhalation is detrimental to respiratory health. Public health interventions should prioritize vulnerable populations during and after volcanic eruptions.